1999
DOI: 10.1016/s0194-5998(99)80139-9
|View full text |Cite
|
Sign up to set email alerts
|

Can patient satisfaction with decisions predict compliance with surgery?

Abstract: Research Forum-Monday P99 the RDI (R = 0.43) and the adenoid size (R = 0.43). Two items with poor validity were dropped, reducing the survey to 18 items (OSA-18). The relationship between the OSA-18 summary score and RDI remained significant when adjusted for tonsil size, adenoid size, body mass index, and child age. Based on the total survey score the impact of OSAS on quality of life was small for 20 children (33%), moderate for 19 (31%), and large for 22 (36%). Conclusions: The OSA-18 is a valid and reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Another factor that also may be important for determining whether a patient cancels prior to surgery is their satisfaction at the original consultation when surgery was decided upon (Parhiscar and Rosenfold, 2002). This study found that the strongest predictor for whether a patient decided to cancel their surgery was their score on an objective “satisfaction with decision” questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that also may be important for determining whether a patient cancels prior to surgery is their satisfaction at the original consultation when surgery was decided upon (Parhiscar and Rosenfold, 2002). This study found that the strongest predictor for whether a patient decided to cancel their surgery was their score on an objective “satisfaction with decision” questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is of particular importance because immunization status (on time, late, or not at all) regarding the first scheduled immunization is an important predictor of whether the child is fully immunized at 2 years of age (Rainger et al, 1998). The significantly higher ratings of satisfaction with the decision and preparedness for the effects of the immunization, both of which have been shown to be associated with “sticking” to the decision (Parhiscar & Rosenfeld, 2002; Wroe & Thomas, 2003), would suggest that the effects may be long-term. However, a longer term study with a larger sample size is necessary to clarify this.…”
Section: Discussionmentioning
confidence: 99%
“…Our interview data suggest that efforts to improve information provision and the processes of decision‐making from women's perspectives may improve women's perceptions of the decision made and reduce the likelihood of subsequent regret. It has been shown in other clinical settings that people with high satisfaction with decision scores are more likely to ‘follow through’ on agreed decisions and attend for scheduled surgery 39 …”
Section: Discussionmentioning
confidence: 99%